Virtual Resource management in Cloud Environment - Ali Heydarzadegan, aser Nemati Faramarz Samsami (International Journal of Scientific Research and Management (IJSRM), 2013)
Cloud computing is a new model for computing. The resource management tools are important compared to traditional distributed systems like grid computing. In order to better management the virtual resource in cloud, an event-driven push (EDP) monitoring model is proposed. EDP can provide comparatively information about usage and status of the resources. The model can simplify the communication between Master and Workers without missing the important events happened during the push interval. We test it by extend the Libvirt in monitoring of virtual CPU and memory.